"Kasserine Island" boundaries variations during the Upper Cretaceous–Eocene (central Tunisia). (November 2015) - Kadri, Ali; Essid, El Mabrouk; Merzeraud, Gilles
Abstract: The emergent domain known as "Kasserine Island" in central Tunisia, to the West of the North–South Axis, was emerging during the Turonian. This area has undergone several changes during the Cretaceous–Eocene period. In the present study, the compilation of surface and sub-surface data provided new information about the boundaries variations of the emerged domain. The analysis of paleogeographic maps allowed the identification of three distinct stages of evolution. The first stage extents from the Middle Turonian to the Lower Maastrichtian where the emergent domain covers the area extending from Jebels Selloum-Sidi Aich in the West to Jebel Bouhedma in the East. The boundaries of this area coincide with the E–W Kasserine fault to the North, the N–S Lessouda-Boudinar fault in the East and the N 120 el Mech-Souinia flexure at the South. This emersion contemporaneous with a high eustatic level is most likely related to tectonic activity. The extensional tectonic regime that is characterized by a NE–SW minimal horizontal stress, has reactivated border faults with a normal component. The interference of the tilting of these border faults was at the origin of the emergence of this domain. The ascent of the Triassic salt may also have contributed in this uplift. In the second stage, the emerged domain has reached its maximum expansion to the North, the West and the South during the Middle Maastrichtian–Paleocene period. Its northern limit is irregular, while the southern limit coincides with the N120 Gafsa fault and the E–W fault of Jebels Orbata-Bouhedma. The N–S Lessouda-Boudinar fault forms the eastern limit. This expansion is mostly related to the global eustatic fall that is well characterized during this period, and partly to the compressive tectonic activity. The Lower Eocene is characterized by a marine transgression that has interested the northern edge of the Island, where the Ypresian deposits are discordant on older series. This edge was irregular and marked by the Gulf of Sbiba. The eastern, the southern, and the western boundaries kept the same shape as that of the previous stage. The compressive tectonic regime, characterized by a NW–SE maximum horizontal stress, is accentuated. This constraint state has generated NE–SW folds and NW–SE grabens. Some of these structures allowed the accumulation of a thick phosphate deposits at their edges, and continental deposits in the emerged area. During the Middle to Upper Eocene, the emergent area narrowed further at the North. The deposits are transgressive and discordant on older series. The Other limits always coincide with the Gafsa fault, the Jebels Orbata-Bouhedma and Jebels Lessouda-Boudinar faults. This period is characterized by the filling of the Gafsa basin by evaporate deposits before its emergence in the Oligocene. As a result, the southern-central Tunisia emerged as one area. Highlights: The "Kasserine Island" is an emerged area in central Tunisia during the Upper Cretaceous–Eocene. The bald area kept the same shape during the Late Cretaceous. The maximum of extension of the bald area was reached during the Paleocene. In the Eocene, the emerged domain was narrowed on the northern side. The spatial evolution of this emerged area was controlled by eustatism and tectonic.